Flexural behavior of hybrid steel fiber reinforced self-consolidating concretes - Dimas Alan Strauss Rambo (Rem: Revista Escola de Minas, 2014)
The simultaneous use of different types of fibers as reinforcement in concrete, mortar or pastes, can avoid the propagation and widening of cracks at different stages of their load-deflection or stress-strain behavior. The purpose of this article is to evaluate the flexural behavior in the material and structural scale of self-compacting concretes reinforced with meso and macro steel fibers. Two tests were used to mechanically characterize the concretes reinforced with volume fractions of 1 and 1.5% hybrid steel fibers: four point bending tests (material scale) and round panel tests (structural scale). The results indicated that hybridization of fiber reinforcement raised the serviceability limit state of concrete, contributing to increased toughness and load bearing capacity for small levels of displacement and crack openings. Such benefits were more evident in the structural tests considering the degree of hyperstaticity and multiple cracking potential of the panels. In the descending branch of the load-displacement curves, where macro-cracks were predominant, macro-fibers were more efficient in increasing the overall capacity for energy absorption of the composites.